Assessment of Chronic Pain in Children: Current Status and Emerging Topics - Tonya Mizell Palermo (Pain Research and Management)
The present paper reviews the current status of research on assessment of chronic pain in children and adolescents, primarily in the context of treatment outcome research. Two specific primary aims are addressed. First, the degree of attention devoted to several major domains of chronic pain assessment (pain, physical functioning, role functioning, sleep and emotional functioning) is summarized, highlighting areas where further instrument development and validation are needed. Second, sensitivity of instruments within these domains is presented using data from clinical trials of psychological therapies aimed at treatment of chronic pain in children and adolescents. Findings demonstrate that although there has been recent progress in developing and validating a range of measures of pain-related outcomes, as of yet, very few clinical trials have included any outcomes other than pain intensity. Moreover, in randomized controlled trials where physical, role or emotional functioning outcomes have been included, there have been limited positive findings. The present paper lists some challenges and future directions in assessment of physical and role functioning, including highlighting emerging methodologies for assessment of physical activity and function in children with chronic pain. Clinical implications of integrating assessment tools into clinical practice are discussed. In conclusion, progress in developing and validating specific tools to assess important outcome domains in chronic pain has been realized. Opportunities exist for further measurement validation in most domains, and further theory-driven treatment research to match goals of the treatment with specific interventions and outcomes.